"I'm coming out!": An autoethnographic situation of sel/f/ves within queer fat chronically Ill identity. (June 2022) - Harrop, Erin Nicole; Kattari, Shanna K.
Highlights: Autoethnography and autoarchaeology can be used to explore coming out as fat. Internal processes when coming out as fat mirror other coming out processes. Community belonging, identity, and critical consciousness were central themes. Fat belonging, identity, and critical consciousness may guard against discrimination. Abstract: In this article, we (two fat, white, queer, nonbinary, chronically ill critical social work scholars) explore the parallel processes of coming out as fat and coming out as other identities (queer, femme, neurodivergent, nonbinary, chronically ill, disabled). We begin by reviewing literature from queer theories, crip theory, and fat studies, addressing concepts of "coming out" and identity. Next, taking an identity-centered autoethnographic and autoarchaeological approach, we explore how the processes in coming out as fat—growing critical consciousness, positive social identity reclamation, community belonging—mirrored other coming out processes, fostering resilience in our lives. We perform this reflection on sense(s) of self within a queer critical intersectional approach, as we individually and collectively examine how our fat identities are situated within our gender, racial, class, ability, health, and sexual orientation contexts. We interrogate how these identities of fatness and beyond, both privileged and oppressed, interplay in our personal, professional, and health-related experiences, and interactions with others. Finally, building off of the theoretical work proposed by Hunger, Major, and Blodorn (2015), we integrate concepts of critical consciousness, positive social identity, and community connectedness into the social identity threat model (as applied to weight stigma), hypothesizing how these potential positive outcomes of "coming out" may moderate the relationship between the psychological stress associated with marginalized identity and the adverse physical and mental health outcomes commonly associated with oppression and minority stress.